Aspects of the Figure. - The Cleveland Museum of Art, Cleveland (Cleveland : The Cleveland Museum of Art, 1974)
Beal, Jack ; Beckman, William ; Bruder, Harold ; Clarke, John Clem ; Hall, Susan ; Hickam, Richard A. ; Hsai, Yan ; Lee-Smith, Hughie ; McLean, Richard ; Midgette, Willard ; Pearlstein, Philip ; Perlis, Donald ; Porter, Fairfield ; Schonzeit, Ben ; Soyer, Raphael ; Thiebaud, Wayne
Aspects of the Figure, The Cleveland Museum of Art, Cleveland, July 10 - September 1, 1974
boek